Neutrophil Suppresses Tumor Cell Proliferation via Fas /Fas Ligand Pathway Mediated Cell Cycle Arrested - Sun, Bingwei (Int J Biol Sci, 2018)
While neutrophils have dutifully performed their function in injury and infection, the recent works have found that cytotoxicity and/or cytostatic of neutrophils has also been observed in tumor. Till now the molecular players that participate in this neutrophils antitumoral effect remain unclear. In the current study, we find that neutrophils from healthy donors have potent suppression to tumor cell lines by physical contact. Importantly, these suppression activities seem to be cancer cell-specific which is not observed in the normal cells. Further observations show that neutrophils mediated tumor cell lines growth inhibitory effect through early cell cycle arrested. Treatment with an antagonist Fas receptor in A549 cell line or knocking out of the Fas gene in A549 cell line recovers tumor cells cycle and lessen neutrophils anti-tumor effect. The interaction between neutrophils and A549 cell line through Fas ligand /Fas regulates the expression of cell cycle checkpoint proteins, leading to early cell cycle arrest. This phenomenon is also seen in other 3 tumor cell lines. Taken together, our results identified a new role of Fas ligand /Fas interaction in neutrophils antitumoral effect in tumors via arresting cell cycle.